2012
DOI: 10.1016/j.jbiomech.2012.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Orientation dependence of progressive post-yield behavior of human cortical bone in compression

Abstract: Identifying the underlying mechanisms of energy dissipation during post-yield deformation of bone is critical in understanding bone fragility fractures. However, the orientation-dependence of post-yield properties of bone is still poorly understood. Thus, the objective of this study was to determine the effect of loading direction on the evolution of post-yield behavior of bone using a progressive loading protocol. To do so, cylindrical compressive bone samples were prepared each in the longitudinal, circumfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 37 publications
(46 reference statements)
1
40
2
5
Order By: Relevance
“…The typical mechanical properties of titanium alloy are 1380-2070 MPa for ultimate bearing strength and 825-895 MPa for yield strength [34]. For the mechanical properties of cortical bone, some previous studies have reported that the failure strength of the human cortical bone ranges from 90 to 200 MPa [35,36]. Our results showed that the maximum stress of cortical bone in model c was less than 90 MPa under axial rotation conditions.…”
Section: Discussionmentioning
confidence: 60%
“…The typical mechanical properties of titanium alloy are 1380-2070 MPa for ultimate bearing strength and 825-895 MPa for yield strength [34]. For the mechanical properties of cortical bone, some previous studies have reported that the failure strength of the human cortical bone ranges from 90 to 200 MPa [35,36]. Our results showed that the maximum stress of cortical bone in model c was less than 90 MPa under axial rotation conditions.…”
Section: Discussionmentioning
confidence: 60%
“…As a control, the E H-S extracted from hard wall F - δ curves, from the polystyrene petri-dish (expected E H-S ~ 3 GPa) under the same experimental conditions, does not exceed 10s to 100s kPa, which is the upper limit of E H-S using the current AFM setup (that is focused on measuring soft components). The experimental setup is not sensitive to the GPa moduli of calcified cortical and trabecular bone previously described (1115), as this is beyond the scope of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the low spring constant cantilever and relatively large contact radius probe were selected for use in the current study after extensive preliminary experiments, and provide sufficient force sensitivity to assess subcellular scale mechanics in soft tissue. This is in contrast to using conventional sharp AFM probes and enables accurate measurements of the soft components in the BMev, rather than simply being able to obtain measurements from the calcified regions (1115).…”
Section: Resultsmentioning
confidence: 99%
“…Enquanto alguns artigos relatam que o osso cortical apresentaria E t diferente do E c 21-26,Mack c (1964, apud 27, 28) ou dão indícios d sobre este comportamento 29,44 ; outros relatam que o osso apresentaria sempre o mesmo E 28, 31, 45-47 , independentemente do carregamento. A maioria dos artigos [48][49][50][51][52][53][54][55][56][57][58][59]…”
Section: Bimodularidade Em Osso Corticalunclassified
“…Nestes ensaios também é importante desconsiderar as deformações sofridas pela máquina, o que pode ser feito com o auxílio de um extensômetro [55][56][57][58] ou descontando as deformações através do cálculo da complacência da máquina de ensaios 61 . O ensaio de flexão em três pontos pode ser empregado para calcular o E em espécimes de secção transversal cilíndrica 59 , retangular [67][68][69][70] ou mesmo em ossos tubulares inteiros 71,72 (o que é muito útil para medir o E de ossos pequenos 65 ).…”
Section: Bimodularidade Em Osso Corticalunclassified